A prospective, single-centre, randomised study evaluating the clinical, imaging and immunological depth of remission achieved by very early versus delayed Etanercept in patients with Rheumatoid Arthritis (VEDERA). Issue 1 (December 2016) - Dumitru, Raluca; Horton, Sarah; Hodgson, Richard; Wakefield, Richard; Hensor, Elizabeth; Emery, Paul; Buch, Maya
Abstract Background Rheumatoid arthritis (RA) is a chronic inflammatory arthritis, with significant impact on quality of life and functional status. Whilst biologic disease modifying anti-rheumatic drugs (bDMARD) such as tumour necrosis factor-inhibitor (TNFi) agents have revolutionised outcomes in RA, early diagnosis with immediate conventional therapy, titrated in a treat to target approach is also associated with high remission rates. The main aim of the VEDERA study (Very Early versus Delayed Etanercept in Rheumatoid Arthritis) is to assess the depth of remission, sustainability of remission and immunological normalisation induced by very early TNFi with etanercept (ETN) or standard of care +/- delayed ETN. Methods/Design VEDERA is a pragmatic, phase IV single-centre open-label randomised superiority trial of 120 patients with early, treatment-naive RA. Patients will be randomised 1:1 to first-line ETN and methotrexate (MTX) or MTX with additional synthetic disease modifying anti-rheumatic drugs (sDMARDs) according to a treat to target (TT) protocol with further step up to ETN and MTX after 24 weeks if remission is not achieved. Participants will have regular disease activity assessments and imaging evaluation including musculoskeletal ultrasound and MRI. The main objective of this study is to assess the proportion of patients with early RA that achieve clinical remission at 48 weeks, following either treatment strategy. In addition, the participants are invited to take part in a cardio-vascular sub-study (Coronary Artery Disease in RA, CADERA), which aims to identify the incidence of cardiovascular abnormalities in early RA. Discussion The hypothesis underlining this study is that very early treatment with first-line ETN increases the proportion of patients with rheumatoid arthritis achieving clinical remission, in comparison to conventional therapy. Trial registration NCT02433184, 23/04/2015